Ultrasound and the biomechanical competence of bone - Nicholson, P F (IEEE transactions on ultrasonics, ferroelectrics, and frequency control, 2008)
Ultrasound is a mechanical wave and consequently has a unique potential to characterize the mechanical properties of bone. In some applications, such as determination of the anisotropic elastic constants of cortical bone specimens, this potential has been realized. In other applications, including the hugely important field of clinical measurements, current ultrasonic techniques struggle to provide information directly relating to mechanical properties. This article reviews the successes and shortcomings of ultrasound as a tool for determination of bone mechanical properties and highlights those new developments likely to bring progress in the future